ANALISIS FAKTOR-FAKTOR PENYEBAB TIDAK TERCAPAINYA TARGET PENERIMAAN PAJAK BUMI DAN BANGUNAN DI KABUPATEN KOLAKA - Asriyana, Desy; Ilham, Surianto; Turi, La Ode (Jurnal Akuntansi Kompetif, 2025)
The purpose of this investigation is to identificate what factors are more dominant in causing the land and building tax revenue to not be achieved in Kolaka Regency from 2019-2023.his research is research using a qualitative descriptive method. This study was conducted at the Kolaka Regency Regional Revenue Agency. Both primary and secondary data sources were used in this study. Researchers used evidence and interviews to gather data. Gathering information, reduction of data, presentation of data, and reaching a conclusion are the methods of data analysis that are employed. The findings of the research show that the more dominant factor causing land and building tax revenues to not be achieved in Kolaka Regency from 2019-2023 is active resistance, namely the existence of taxpayers who try to avoid tax objects and passive resistance, namely the lack of economy which can make it difficult to pay taxes. earth and buildings. Keywords: Factors Causing Non-achievement of Land and Building Tax Revenues